Penentuan Cadangan Premi Asuransi Jiwa Bersama Dwiguna dengan Metode Canadian - Darma Ekawati; Fardinah (Journal of Mathematics: Theory and Applications, 2020)
Premium reserve is a number of funds that need to be raised by insurance company in preparation for the payment of claims when the policyholder dies. One of the simplest methods to calculate premium reserving is the prospective premium reserve modified using Canadian method which is a modification of the prospective method. Calculation in this study is using Indonesian Mortality Table (TMI) 2011 This study aims to determine the premium reserves using the Canadian method of endowment joint life insurance. Joint life insurance participants in this study are limited to 2 people. The calculation of premium reserves in this study using TMI 2011, starting with calculating the value of annuities, net annual premiums, annual premiums modified based on the Canadian method, and premium reserves at the end of the t-year in the endowment joint life insurance.